Impact of positive and negative corporate social responsibility on corporate financial performance and idiosyncratic risk - Lin, Woon Leong; Ho, Jo Ann; Ng, Siew Imm; Lee, Chin (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
Despite growing interest for corporate social responsibility (CSR) in the literature, the relationship between CSR activities and idiosyncratic risk of firms, one of the critical components in evaluating shareholder value, has been a topic of scarce examination. Further, the moderating role of firm size on the link between CSR and idiosyncratic risk has not been studied. Existing research on the financial implications of CSR for firms has predominantly focused on positive aspects of CSR, over-looking that companies also undertake actions and initiatives that qualify as corporate social irresponsibility or negative CSR. This study dichotomizes CSR activities into two dimensions, socially responsible activities (positive CSR) and socially irresponsible activities (negative CSR), to scrutinize the distinct effects of the two extents. The authors demonstrate how positive and negative CSR can influences corporate financial performance (CFP) and idiosyncratic risk of firms and discuss the role of firm size as a moderator in the relationship. The proposed hypothesis for the framework and its theoretical justification are discussed in this paper.